The New Caledonian endemic geocorine bug genus, Nannogermalus is not monotypic anymore (Heteroptera: Lygaeoidea: Geocoridae) - Kóbor, Péter (Zootaxa, 2023)
Three new species of the big-eyed bug genus Nannogermalus Kondorosy & Kóbor, 2020 (Hemiptera: Heteroptera: Lygaeoidea: Geocoridae: Geocorinae) are now described: N. herczeki sp. nov., N. pallgergelyi sp. nov. and N. webbi sp. nov. Additions and corrections to the generic description of the genus were made based on the newly acquired morphological knowledge. Key, diagnoses and distribution data for new species of the genus are provided. Ecological notes are given based on collection site data and literature regarding other geocorid taxa.